Math, asked by simranshoker48, 3 months ago

prove the following​

Attachments:

Answers

Answered by harshb77
1

Answer:

cos({sin}^{ - 1}  \frac{3}{5}  +  {cot}^{ - 1}  \frac{3}{2} ) \\  = cos( {tan}^{ - 1} \frac{ \frac{3}{5} }{ \sqrt{1 -  { (\frac{3}{5}) }^{2} } }   +  {tan}^{ - 1}  \frac{2}{3} ) \\  = cos( {tan}^{ - 1}  \frac{ \frac{3}{5} }{ \sqrt{1 -  \frac{9}{25} } }  + \:  {tan}^{ - 1}  \frac{2}{3} ) \\  = cos( {tan}^{ - 1}  \frac{ \frac{3}{5} }{ \sqrt{ \frac{25 - 9}{25} } }  +  {tan}^{ - 1}  \frac{2}{3}  \\  = cos( {tan}^{ - 1}  \frac{ \frac{3}{5} }{ \frac{4}{5} }  +   {tan}^{ - 1}  \frac{2}{3} ) \\  = cos( {tan}^{ - 1}  \frac{3}{4}  +  {tan}^{ - 1}  \frac{2}{3} ) \\  = cos( {tan}^{ - 1} ( \frac{ \frac{3}{4}  +  \frac{2}{3} }{1 -  \frac{3}{4} \times  \frac{2}{3}  } )) \\  = cos( {tan}^{ - 1}  \frac{17}{6} ) \\   \\  = cos( {cos}^{ - 1}  \frac{1}{ \sqrt{1  +  ( \frac{17}{6} )^{2} } } ) \\  =  \frac{1}{ \sqrt{1 +  \frac{289}{36} } }  \\  =  \frac{1}{ \sqrt{ \frac{36 + 289}{36} } }  \\  =  \frac{6}{ \sqrt{325}}  \\  =  \frac{6}{ \sqrt{25 \times 13} }  \\  =  \frac{6}{5 \sqrt{13} }

Similar questions